Development and Implementation of a Cloud-Based Meningitis Surveillance and Specimen Tracking System in Burkina Faso, 2018. (31st October 2019) - Diallo, Alpha Oumar; Kiemtoré, Tanga; Bicaba, Brice Wilfried; Medah, Isaïe; Tarbangdo, Tiga Félix; Sanou, Simon; Soeters, Heidi M; Novak, Ryan T; Aké, Honoré Flavien
Abstract: Nationwide case-based meningitis surveillance was established in Burkina Faso following the introduction of meningococcal serogroup A conjugate vaccine in 2010. However, timely tracking and arrival of cerebrospinal fluid specimens for confirmation at national reference laboratories remained suboptimal. To better understand this gap and identify bottlenecks, the Burkina Faso Ministry of Health, along with key partners, developed and implemented a cloud-based System for Tracking Epidemiological Data and Laboratory Specimens (STELAB), allowing for timely nationwide data reporting and specimen tracking using barcodes. STELAB was adapted to Burkina Faso's infrastructure to ensure suitability, functionality, flexibility, and sustainability. We describe the design, development, and implementation of STELAB. In addition, we discuss strategies used to promote sustainability, lessons learned during the first year of implementation, and future directions. STELAB's novel design and country-driven approach has the potential to achieve sustainable real-time data reporting and specimen tracking for the first time in sub-Saharan Africa.